Cost implications for certified Green Building Index buildings - Chong, Heap Yih; Tam, V.; Lai, W.; Sutrisna, M.; Wang, X.; Illankoon, I. (2017)
The impact of worsening global weather conditions has led to a growing awareness of the importance of sustainability in the global context, including in Malaysia. As a consequence, the Green Building Index rating tool was adopted in Malaysia from 2009 as a yardstick to guide the green buildings. The research aims to identify the initial cost premium for a residential green building to achieve certified green status with the use of basic green options. The primary data were mainly collected from bills of quantities, semi-structured discussions with project personnel, cost experts and suppliers. Finally, a sensitivity analysis is also carried out to analyse the impact of incremental costs to the changes in prices of green material. The findings show an incremental cost of 2·2% of the contract sum to develop a certified residential green building with basic green options. The research provides cost guidelines about the actual premium needed to embark on green building projects. The outcomes of this research can support the decisions of the developer to promote a greener-built environment.